Incidence and predictors of new‐onset constipation during acute hospitalisation after stroke. Issue 4 (6th February 2015) - Lim, S.‐F.; Ong, S. Y.; Tan, Y. L.; Ng, Y. S.; Chan, Y. H.; Childs, C.
Summary: Objectives: We investigated new‐onset constipation in patients with stroke compared with orthopaedic conditions and explored the predictors associated with constipation during acute hospitalisation. Methods: This was a prospective matched cohort study of 110 patients comparing stroke patients ( n = 55) with orthopaedic patients ( n = 55) admitted to a large tertiary acute hospital. Both cohorts were matched by age and sex. The incidence of new‐onset constipation which occurred during a patient's acute hospitalisation was determined. Demographics, comorbidity, clinical factors, laboratory parameters and medications were evaluated as possible predictors of constipation. Results: The incidence of new‐onset constipation was high for both stroke (33%) and orthopaedic patients (27%; p = 0.66). Seven stroke patients (39%) and four orthopaedic patients (27%) developed their first onset of constipation on day 2 of admission. Mobility gains (RR 0.741, p < 0.001) and the use of prophylactic laxatives (RR 0.331, p < 0.01) had a protective effect against constipation. Bedpan use (RR 2.058, p < 0.05) and longer length of stay (RR 1.032, p < 0.05) increased the risk of developing new‐onset constipation. Conclusions: New‐onset constipation is common among patients admitted for stroke and orthopaedic conditions during acute hospitalisation. The early occurrence, on day 2 of admission, calls for prompt preventive intervention for constipation. Abstract : Linked Comment: Ruhnke and Meltzer. Int J Clin Pract 2015; 69: 388–9 .